KONTRIBUSI POWER OTOT TUNGKAI DAN KELENTUKAN TERHADAP KEMAMPUAN TENDANGAN SABIT ATLET PERGURUAN SILAT TAPAK SUCI MUNGKA - Muhammad Fauzil; Yendrizal; Jeki Haryanto; Juanda Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study is the low roundhouse kick performance of athletes from Tapak Suci Mungka, which is influenced by the physical components of leg muscle power and flexibility. This study aimed to determine the contribution of leg muscle power and flexibility to the roundhouse kick ability of Tapak Suci Mungka athletes. The population consisted of 27 athletes, with 17 selected through purposive random sampling. Leg muscle power was measured using the Standing Broad Jump Test, flexibility was assessed using the Side Split Test, and roundhouse kick ability was evaluated using a roundhouse kick performance test. Data were analyzed using the Pearson product-moment correlation and simple regression analysis. The results showed that leg muscle power made a significant contribution to roundhouse kick ability, with an R Square value of 0.700, indicating a contribution of 70%, while the remaining 30% was explained by other factors. Flexibility also contributed significantly, with an R Square value of 0.505, indicating a contribution of 50.5%, while 49.5% was attributed to other factors. Simultaneously, leg muscle power and flexibility contributed 72.4% to roundhouse kick ability, while the remaining 27.6% was influenced by variables not examined in this study.